2008
DOI: 10.1002/pon.1367
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and PTSD symptomatology among colorectal cancer survivors: a 3‐month longitudinal examination of cognitive processing

Abstract: Introduction The experience of cancer can be understood as a psychosocial transition, producing both positive and negative outcomes. Cognitive processing may facilitate psychological adjustment. Methods Fifty-five post-treatment, colorectal cancer survivors (M=65.9 years old; SD=12.7), an average of thirteen months post-diagnosis, were recruited from a state cancer registry and completed baseline and three-month questionnaires assessing dispositional (social desirability), cognitive processing (cognitive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
150
2
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 60 publications
17
150
2
12
Order By: Relevance
“…Some studies have reported a positive relationship (e.g., Wild & Paivio, 2003), whereas others have found a negative relationship (e.g., Hall et al, 2008), some a curvilinear relationship (e.g., Kleim & Ehlers, 2009), and others no relationship at all (e.g., Cordova et al, 2007;Salsman et al, 2009). Contradictory results of the impact of benefit finding on posttraumatic outcomes have been attributed to problems of measurement.…”
Section: Are Posttraumatic Changes Long Lasting?mentioning
confidence: 96%
“…Some studies have reported a positive relationship (e.g., Wild & Paivio, 2003), whereas others have found a negative relationship (e.g., Hall et al, 2008), some a curvilinear relationship (e.g., Kleim & Ehlers, 2009), and others no relationship at all (e.g., Cordova et al, 2007;Salsman et al, 2009). Contradictory results of the impact of benefit finding on posttraumatic outcomes have been attributed to problems of measurement.…”
Section: Are Posttraumatic Changes Long Lasting?mentioning
confidence: 96%
“…The recovery process occurs in a manner and pace unique to each individual (Appleton et al, 2013). The survivor may engage in a period of post-traumatic growth, using techniques including goal setting, meaning making and benefit finding to return to, or reconceptualize 'normal' life (Appleton et al, 2013;Chambers et al, 2012a;Nikoletti et al, 2008;Palmer et al, 2013;Salsman et al, 2009;Soerjomataram et al, 2012).…”
Section: The Process Beginning At Diagnosismentioning
confidence: 99%
“…El concepto de crecimiento postraumático incluye respuestas como el aumento de la autoestima, mayor apreciación de la vida y su significado, aumento de la espiritualidad, más sentimientos de calma o paz y de sentido (9) . La mayoría de estudios científicos psicooncológicos llevados a cabo en mujeres con cáncer de mama concluyen que el ajuste psicológico es mucho más adecuado cuando las mujeres encuentran sentido a la experiencia (10,11) , tras los tratamientos tienen menos secuelas emocionales negativas (12)(13)(14)(15) , se cuidan más durante el tratamiento, y una vez acabado, llevan una vida más saludable, con un mayor compromiso con su salud (7) . A la vista de estos resultados, podría decirse que las mujeres que muestran mayores niveles de resiliencia o mayor crecimiento postraumático aprovechan los aspectos positivos que pueden extraer de la enfermedad.…”
Section: Introductionunclassified